JAVANESE LANGUAGE INTERFERENCE IN THE PRONUNCIATION OF ENGLISH PHONEMES - Wardani, Niasisca Agustia; Suwartono, Tono (University of Muhammadiyah Malang, 2019)
The objective of this research was to investigate the difficulties encountered by Javanese learners inpronouncing the English phonemes and identify factors affecting their pronunciation of the phonemesin the Department of English Language Teaching of Universitas Muhammadiyah Purwokerto (UMP). The researcher used survey as the research method. The population in this research was 6th and 8th semester students who had already passed pronunciation and phonetics subject. While the samples are those who had Javanese background. The data was collected through pronunciation test in a form of audio recording and interview. The major findings of this research are 1) the researcher found that the Javanese learners of English encountered difficulties in pronouncing 13 consonant sounds /ʒ, v, θ, ð, z, ʃ, f, g, k, d, ʧ, ɳ, j/ and 17 vowel sounds /æ, ɛə, i:, eɪ, aʊ, ə:, ɔ:, u:, ɒ, ɪə, əʊ, ʊ, ɑ:, ɪ, ʊə, ɔɪ, aɪ/. While the rest, 14 English sounds /p, b, t, s, h, ʤ, m, n, l, r, w, ʌ, ə, ɛ/ were clearly pronounced by the Javanese learners of English. 2) There are four factors influencing Javanese in learning English pronunciation, among others are; age, first language, exposure, and motivation.